2021
DOI: 10.7150/thno.61875
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary circulation-mediated heart targeting for the prevention of heart failure by inhalation of intrinsically bioactive nanoparticles

Abstract: Heart failure is a serious clinical and public health problem. Currently there is an unmet demand for effective therapies for heart failure. Herein we reported noninvasive inhalation delivery of nanotherapies to prevent heart failure. Methods: A reactive oxygen species (ROS)-scavenging material (TPCD) was synthesized, which was processed into antioxidative and anti-inflammatory nanoparticles ( i.e. , TPCD NP). By decoration with a mitochondrial-targeting moiety, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 79 publications
0
16
0
Order By: Relevance
“…Modification of nanoparticles with different components facilitates mitochondrial directed drug penetration [126]. A team has constructed a non invasive aerosol inhalation delivery system based on antioxidant nano drugs, which can target damaged mitochondria, clear ROS, and improve the targeting ability of nano-drugs to myocardium [85]. Artificial hybrid nanozymes created by protein reconstruction technology and nanotechnology can target mitochondria and scavenge ROS, thereby reducing mitochondrial oxidative damage [127].…”
Section: Nanomaterials Targeted Mitochondria To Improve Mitochondrial...mentioning
confidence: 99%
“…Modification of nanoparticles with different components facilitates mitochondrial directed drug penetration [126]. A team has constructed a non invasive aerosol inhalation delivery system based on antioxidant nano drugs, which can target damaged mitochondria, clear ROS, and improve the targeting ability of nano-drugs to myocardium [85]. Artificial hybrid nanozymes created by protein reconstruction technology and nanotechnology can target mitochondria and scavenge ROS, thereby reducing mitochondrial oxidative damage [127].…”
Section: Nanomaterials Targeted Mitochondria To Improve Mitochondrial...mentioning
confidence: 99%
“…A previous study demonstrated that inhalation-based delivery of TPCD nanoparticles suppressed doxorubicin-induced heart failure in mice due to internalization in cardiomyocytes and scavenging excessive ROS. 347 Moreover, Vanillyl alcohol (PVAX)-polymer nanoparticles treatment alleviated doxorubicin-induced cardiomyopathy by inhibiting activation of poly (ADP ribose) polymerase 1 (PARP-1) and caspase-3. 348 Experimental results from a rodent diabetic cardiomyopathy model revealed that inhalation of calcium phosphate nanoparticles loaded with a therapeutic mimetic peptide markedly improved myocardial contraction and cardiac function via rapid translocation of calcium phosphate nanoparticles from pulmonary to myocardium, where the therapeutic mimetic peptide is quickly released.…”
Section: Nanoparticle-based Therapeutic Methods For Vascular Aging-re...mentioning
confidence: 99%
“…133 In another study, Liu et al adopted a new approach to deliver nanoparticles for the treatment of heart failure. 134 They used triphenylphosphine-modified ROS-scavenging nanoparticles for targeting mitochondria by non-invasive inhalation. Taking advantage of the ability of particles smaller than 100 nm to enter the pulmonary circulation and accumulate in the heart through the air-blood barrier, nanoparticles deposited in the lungs were continuously delivered to the heart through the pulmonary circulation, internalized to cardiomyocytes, and scavenged ROS to treat heart failure.…”
Section: Nanoparticle Targeting Specific Organs and Their Designmentioning
confidence: 99%